2017
DOI: 10.1111/jtxs.12286
|View full text |Cite
|
Sign up to set email alerts
|

Effects of concentrated and dephytinized wheat bran and rice bran addition on bread properties

Abstract: Consumption of dietary fiber offers a range of health benefits. Cereal bran has great potential as a dietary fiber source. However, this bran's high phytic acid content and adverse effects on bread quality limit that potential. It is possible to obtain high dietary fiber and low phytic acid bran samples through bran concentration and dephytinization treatments. The dephytinization treatment is an effective method for degradation of phytic acid. The negative effects of wheat bran and rice bran on bread quality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 53 publications
3
23
0
Order By: Relevance
“…Maurer et al (2019) reported an amelioration of colitis in rats feed with grape peels, the DF being responsible for the intestinal barrier function reestablishment, whereas the phenolic compounds bounded to fiber fractions contributed to the cecal metabolism restoration, improving the production of beneficial compounds such as cecal shortchain fatty acids with anti-inflammatory and antiproliferative effects on the colonic cells and reducing the activation of the unfolded protein response (Maurer et al, 2019;Yuan, Wang, Chen, Zhu, & Cao, 2016). DF presents many biological functions such as anticancer activity, gastrointestinal activity improvement, antiapoptotic activity, cardiovascular disease prevention, antihypercholesterolemic activity, and anti-hyperglycemia effect (Kurek & Wyrwisz, 2015;Özkaya, Baumgartner, & Özkaya, 2018;Zhu et al, 2014).…”
Section: Effects Of Grape Byproducts Addition On the Nutritional Charmentioning
confidence: 99%
“…Maurer et al (2019) reported an amelioration of colitis in rats feed with grape peels, the DF being responsible for the intestinal barrier function reestablishment, whereas the phenolic compounds bounded to fiber fractions contributed to the cecal metabolism restoration, improving the production of beneficial compounds such as cecal shortchain fatty acids with anti-inflammatory and antiproliferative effects on the colonic cells and reducing the activation of the unfolded protein response (Maurer et al, 2019;Yuan, Wang, Chen, Zhu, & Cao, 2016). DF presents many biological functions such as anticancer activity, gastrointestinal activity improvement, antiapoptotic activity, cardiovascular disease prevention, antihypercholesterolemic activity, and anti-hyperglycemia effect (Kurek & Wyrwisz, 2015;Özkaya, Baumgartner, & Özkaya, 2018;Zhu et al, 2014).…”
Section: Effects Of Grape Byproducts Addition On the Nutritional Charmentioning
confidence: 99%
“…Cereal brans are generally used in various foods to improve their nutritional profile with special reference to dietary fibers (Han et al., 2019). In recent years, interest in dietary fiber has been improved owing to its health benefits such as diabetes, coronary heart disease, hypertension, stroke, and cancer (Özkaya et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…It has several functions like enhancing water absorption, lowering tolerance for dough strength, mixing, fermentation, and dough stickiness improved, when maize bran is incorporated into the flour. Thus, the incorporation of cereal bran leads to lower loaf volume, crumb softness, specific volume, and causes darker crumb color and coarser crumb texture (Özkaya et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In general, bran is used for the biofortification of refined wheat flour used for breadmaking and other bakery goods. Bread biofortification with bran or whole meal of maize, rice, oat, rye, barley and wheat results in technological changes such as the decrease in loaf bread volume, while the content of water, mineral content, fibres, phytates and antioxidant activity are increased and, in addition, the quality of volatile compounds is also affected [43][44][45][46]. The presence of bran in bakery is linked with increased water absorption and low loaf volume due to the weakening of the dough structure from the disruption of the gluten network.…”
Section: Processing Of Cereals and The Derived By-productsmentioning
confidence: 99%